2000
DOI: 10.1037/0735-7028.31.2.179
|View full text |Cite
|
Sign up to set email alerts
|

Telehealth and neuropsychological assessment: New opportunities for psychologists.

Abstract: The advent of telehealth technology gives psychologists new opportunities to expand their practices in a cost-effective manner, but little is known about telehealth efficacy and costs. This study of 49 neuropsychology clients interviewed using videoconferencing and 49 matched in-person controls yielded no group differences in client ratings of interpersonal factors. Telehealth clients were more likely to want to repeat their experience, but psychologist satisfaction was lower foe telehealth sessions. Telehealt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
91
0
2

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(100 citation statements)
references
References 7 publications
7
91
0
2
Order By: Relevance
“…It is noteworthy that virtually all participants with prior psychotherapy experience in the present project reported that FPS was more helpful than prior experiences with psychotherapy. Other investigators (see Schopp, Johnstone, & Merrell, 2000) have also found that telehealth clients report more positive experiences than their face-to-face counterparts. Although the accessibility of on-line FPS likely contributed to this preference, participants also noted the structured nature of the intervention and its emphasis on building skills and solving problems.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…It is noteworthy that virtually all participants with prior psychotherapy experience in the present project reported that FPS was more helpful than prior experiences with psychotherapy. Other investigators (see Schopp, Johnstone, & Merrell, 2000) have also found that telehealth clients report more positive experiences than their face-to-face counterparts. Although the accessibility of on-line FPS likely contributed to this preference, participants also noted the structured nature of the intervention and its emphasis on building skills and solving problems.…”
Section: Discussionmentioning
confidence: 97%
“…Previous researchers (Kleiner, Akers, Burke, & Werner, 2002;Schopp et al, 2000) have reported that clinicians are less comfortable with incorporating new technology into their practice than are the consumers of health services. Likewise, the therapist in this study noted the awkwardness of not being able to clearly see and hear all participants at all times.…”
Section: Discussionmentioning
confidence: 99%
“…Some research focused on whether face-to-face counseling or online counseling is effective, the results indicate that both counseling types are effective (Magaletta, Fagan, & Peyrot, 2000). Other research focused of which type of counseling is preferred by clients and results from that study indicate that people prefer online counseling over faceto-face counseling (Schopp, Johnstone, & Merrell, 2000).…”
Section: Introductionmentioning
confidence: 94%
“…44 A study on use of telemedicine for clients at a rural hospital found that telemedicine was cheaper than face-to-face options and received similar ratings from clients, though there were lower ratings for video conferencing from psychologists. 45 Obsessive-Compulsive Disorder. The studies in this group [46][47][48] made use of the computer-aided system BT STEPS, which has an interactive voice response approach.…”
Section: General Psychiatric and Mental Health Servicesmentioning
confidence: 99%